Evaluation Study of the High Yielding Varieties Programme - Planning Commission (Planning Commission, 1968)
This report is based on the data collected during rabi 1967.68 for wheat, paddy and jowar crops. The objectives, design and methodology of field investigation followed were the same as in the kharif. season. The study for wheat was carried out in 15 districts and as many blocks in 6 States and a sample of 441 participants and 192 non. participants in 45 selected villages was drawn for collection of detailed data. There was no participant cultivator in the three selected villages of Ahmednagar district, Maharashtra and hence data from the non .participants only was collected and analysed. For paddy the study could be conducted in 10 out of 22 selected blocks of kharif season while for jowar 4 of the selected blocks (three in Maharashtra and one in Mysore) were retained.
Report for Rabi 1967-68 Wheat, Paddy and Jowar